2018
DOI: 10.1016/j.ijdevneu.2018.08.007
|View full text |Cite
|
Sign up to set email alerts
|

NGF, TrkA‐P and neuroprotection after a hypoxic event in the developing central nervous system

Abstract: A decrease in the concentration of oxygen in the blood and tissues (hypoxia) produces important, sometimes irreversible, damages in the central nervous system (CNS) both during development and also postnatally. The present work aims at analyzing the expression of nerve growth factor (NGF) and p75 and the activation of TrkA in response to an acute normobaric hypoxic event and to evaluate the possible protective role of exogenous NGF. The developing chick optic tectum (OT), a recognized model of corticogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…We therefore constructed a small library of reporter constructs in which Firefly luciferase expression is driven by a repetitive linear organization of four transcription factor consensus binding sites ( Figure 3 schematic drawing of reporter gene cassette and Table S28 ). These regulatory sequences included desoxyribonucleic acid (DNA)-binding transcription factors that are known to act upstream of ngfβ expression [ 14 , 15 ]. The constructs were transfected into 1321N1 cells together with a plasmid expressing Renilla luciferase under control of the cytomegalovirus (CMV) promoter in the pCS2+ vector backbone [ 16 ] to normalize expression data for differences in transfection efficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore constructed a small library of reporter constructs in which Firefly luciferase expression is driven by a repetitive linear organization of four transcription factor consensus binding sites ( Figure 3 schematic drawing of reporter gene cassette and Table S28 ). These regulatory sequences included desoxyribonucleic acid (DNA)-binding transcription factors that are known to act upstream of ngfβ expression [ 14 , 15 ]. The constructs were transfected into 1321N1 cells together with a plasmid expressing Renilla luciferase under control of the cytomegalovirus (CMV) promoter in the pCS2+ vector backbone [ 16 ] to normalize expression data for differences in transfection efficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly a first step towards understanding the mechanisms of action for the activity of erinacine C is needed. This could be guided by analyzing several signaling pathways and their DNA-binding transcription factors including those that are known to act upstream of ngf expression [ 14 , 15 ]. We have therefore set out to elucidate erinacine C mediated signal transduction events by analyzing altered transcriptional processes in erinacine C treated astroglial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of NGF and TrkA may further activate the MAPK signaling pathway and promote stem cell proliferation and differentiation (30,31). Numerous studies have indicated that the TrkA receptor may be detected on MSCs, and TrkA receptor expression is significantly increased under HG and ischemic conditions (32)(33)(34). The present study indicated that mainly through the TrkA receptor, NGF protected MSCs against HG damage and enhanced their anti-inflammatory effect in diabetes.…”
Section: Discussionmentioning
confidence: 55%
“…Increased segregation of NGF in the brain of these foals cannot be excluded, and the authors speculate that this change primarily reflects the brain compartment, as suggested by studies conducted in human perinatology, showing that blood levels of neurotrophins are similar to those in the brain [48], changing in infants with neurological disorders due to clinical states of prolonged perinatal hypoxia [49]. In vitro and in vivo animal models have also shown that hypoxia-induced cell death is preceded by a period of NGF up-regulation, suggesting that NGF plays a protective role [53]. In the same direction, clinical studies conducted on infants with hypoxic-ischemic brain injury and treated with intraventricular NGF infusion showed a significant clinical improvement in their neurological condition [54,55], and increased NGF and VEGF segregation in asphyxiated foals may protect neurons against protracted injury.…”
Section: Discussionmentioning
confidence: 88%